Analisis Pelaksanaan Program Pemberantasan DBD dan Tingkat Keberhasilan Pencegahan dan Pengendaliannya di Puskesmas Wilayah Kabupaten Kotawaringin Barat - Julkifnidin, Julkifnidin, Yuli Kusumawati, S.KM., M.Kes. (Epid), Heru Subaris Kasjono, S.KM., M.Kes (2016)
DHF is a public health problem in Indonesia that the number of sufferers is likely to increase, and spread more widely, and often lead to extraordinary events and death. This study aimed to analyze of implementation of the dengue eradication program, and level of the success of prevention and control of DHFat the public health center of Region of Kotawaringin Barat District. This type of research is observational research with descriptive analysis of quantitative and equipped with qualitative. The study population was all healthcare workers who hold the DHF program and environmental health program and the documents of implementation of dengue eradication programs. The research sample using total sampling technique, as many as twenty eigth respondens and documents of implementation of dengue eradication programs in fourteen health centers. The results showed that of the seven implementation of eradicate dengue programs should be carried out, there are three programs as a whole is not implemented, namely the program of larva monitoring periodically once every three months (100%), program of health promotion of DHF routine (100%), and program of sectoral formation of the working group of DHF (100%). While the success rate of prevention and control of dengue indicates that there are nine health centers were declared unsuccessful (64.3%). The researchers suggest that every health center implemented programs that have not been executed and enhance programs that have been implemented, especially mobilize the communities in mosquito eradication activities regularly ones every month, and conduct mass abatisasi evenly in the working area once every three months.